Pengalaman Guru PAUD Di Kota Banjarmasin Tentang Integrasi Teknologi Dalam Pembelajaran - Nor Izzatil Hasanah; Aspiya Aziza (UIN Sultan Maulana Hasanudin Banten, 2024)
In Education, technology integration can be categorized into three: technology for learning preparation, technology as learning media, and technology as a learning tool. This research aims to describe the experiences of PAUD teachers in Banjarmasin City in integrating technology into learning. This research used mixed methods and, an embedded design approach, and involved 232 teachers. The research instrument is an online questionnaire with closed and open questions which are analyzed descriptively and thematically. The research results show that the majority of teachers have integrated technology for learning preparation and learning media and only a small number of teachers in early childhood education in the city of Banjarmasin use technology and digital devices as learning tools. Low teacher competence and the lack of supporting facilities are considered to be influencing factors. Therefore, evenly supporting facilities, and increasing the competence of teachers regarding technology integration in PAUD institutions through seminars, workshops, and training is very necessary.